2015
DOI: 10.1142/s2339547815200034
|View full text |Cite
|
Sign up to set email alerts
|

A novel low-volume two-chamber microfabricated platform for evaluating drug metabolism and toxicity

Abstract: To evaluate drug and metabolite efficacy on a target organ, it is essential to include metabolic function of hepatocytes, and to evaluate metabolite influence on both hepatocytes and the target of interest. Herein, we have developed a two-chamber microfabricated device separated by a membrane enabling communication between hepatocytes and cancer cells. The microscale environment created enables cell co-culture in a low media-to-cell ratio leading to higher metabolite formation and rapid accumulation, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…However, under static conditions in conventional cell culture dishes, unfavorable high media-to-cell volume ratios exist. Recently, it was shown that decreasing media-to-cell volume ratios resulted in the formation of higher concentrations of drug metabolites [54]. Cell culture of 3 Â 10 5 HepaRG/LX-2 cells in MOTiF biochips requires only 120 ml of culture medium (0.4 nl/hepatocyte) making it a suitable tool for substance screening on a micro-scale basis with minimized wastage of test compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, under static conditions in conventional cell culture dishes, unfavorable high media-to-cell volume ratios exist. Recently, it was shown that decreasing media-to-cell volume ratios resulted in the formation of higher concentrations of drug metabolites [54]. Cell culture of 3 Â 10 5 HepaRG/LX-2 cells in MOTiF biochips requires only 120 ml of culture medium (0.4 nl/hepatocyte) making it a suitable tool for substance screening on a micro-scale basis with minimized wastage of test compounds.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the recently emerged organ-on-a-chip systems that combine advanced microfluidic technologies and tissue engineering approaches to simulate both the biology and physiology of human organs have been developed (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31).…”
Section: Significancementioning
confidence: 99%
“…46,47 Multiwell plates are convenient and widely used cell culture platforms that provide an environment resulting in a typical culture media of *1 nL/hepatocyte in the case of monolayer culture of hepatocytes. Cell culture platforms can be broadly divided and evaluated based on the amount of media per hepatocyte (Fig.…”
Section: Progress In Hepatic Cells For Use In Liver Platformsmentioning
confidence: 99%
“…It is important to note that despite achieving relatively lower media volume/hepatocyte ratio in the static microfabricated system, it remains an order of magnitude higher than in vivo, based on simple scaling consideration (blood volume/hepatocyte). 46 Another important consideration for these systems is the relative throughput especially if they intend to be used at the drug screening stage. By far, multiwell plate static configuration offers the highest throughput followed by static microfabricated systems and lastly the modular macroscale bioreactor and microfluidic flow platforms.…”
Section: Progress In Hepatic Cells For Use In Liver Platformsmentioning
confidence: 99%
See 1 more Smart Citation